The THE EFFECT OF LIVE MUSIC ON CUSTOMER SATISFACTION AND SALES INCREASE AT CIMAHI COFFEE BENTO CAFÉ - Leni Amalia, Annisa; Himayatu Amali, Naza (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study discusses the effect of live music on customer satisfaction and increased sales at Bento Kopi Cafe. This cafe is located in Cimahi, and has utilized live music as an attraction for customers. The purpose of this study was to determine the extent of the influence of live music on customer satisfaction and its impact on increasing sales. The method used is descriptive quantitative, with data collection through questionnaires to 100 respondents. With the sampling technique carried out by purposive sampling method with the condition that customers have come on a day with live music and a day without live music. The data collection technique used in this research is a questionnaire. The data analysis technique used in this study is linear regression.